2016
DOI: 10.3904/kjim.2014.390
|View full text |Cite
|
Sign up to set email alerts
|

Association of autophagy related gene polymorphisms with neutrophilic airway inflammation in adult asthma

Abstract: Background/Aims:Role of autophagy in neutrophil function and the association of autophagy and autophagy related (ATG) gene polymorphisms with asthma susceptibility were suggested. In this study, we investigated the genetic association of ATG5 and ATG7 polymorphisms with asthma risk, severity and neutrophilic airway inflammation.Methods:We recruited 408 asthma patients and 201 healthy controls. Sputum neutrophil counts were determined by H&E staining. Serum interleukin 8 (IL-8) levels were measured by enzyme-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 36 publications
2
52
0
Order By: Relevance
“…Furthermore, the finding that Dex and CAM induced autophagy in neutrophils was consistent with the previous reports . We suggested previously that autophagy‐related ( ATG ) 5 and ATG7 polymorphisms could contribute to neutrophil activation and function . Consistently, deleting Atg5 and Atg7 in mice was found to reduce neutrophil degranulation and neutrophil‐mediated inflammation .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the finding that Dex and CAM induced autophagy in neutrophils was consistent with the previous reports . We suggested previously that autophagy‐related ( ATG ) 5 and ATG7 polymorphisms could contribute to neutrophil activation and function . Consistently, deleting Atg5 and Atg7 in mice was found to reduce neutrophil degranulation and neutrophil‐mediated inflammation .…”
Section: Discussionsupporting
confidence: 91%
“…Atopy was identified as described previously . Sputum neutrophil and eosinophil counts were evaluated as described in a previous study .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…How autophagy shapes the inflammatory response has been discussed in various disease models6789, and several studies have focused on the functional link between autophagy and inflammation-associated pulmonary pathogenesis, which suggest a critical role of autophagy in inflammation regulation in pulmonary diseases like asthma and acute lung injury (ALI)1011. On the other hand, emerging investigations have demonstrated that autophagy can be activated by CS in lung cells1213, acting as a deleterious process during COPD pathogenesis such as the apoptosis of lung epithelial cells1314.…”
mentioning
confidence: 99%
“…Abundant studies reported that airway neutrophilic inflammation was associated with asthma phenotypes/endotypes, severe asthma, asthma exacerbations, and corticosteroid treatment responses [38] .…”
Section: Involvement Of Neutrophils In Airway Inflammation Of Asthmamentioning
confidence: 99%